Penerapan Strategi See Think Wonder untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Buku Fiksi dan Nonfiksi Kelas VII SMPN 1 Masbagik - Juliana Putri Putri; Hilmiyatun; Saufian Anhari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to improve students’ critical thinking skills through the application of the See, Think, Wonder strategy in Indonesian language learning on fiction and nonfiction books. The research was conducted based on initial observations indicating that students’ critical thinking skills were relatively low, particularly in observing information, analyzing reading content, expressing logical opinions, and drawing conclusions. This Classroom Action Research employed a qualitative descriptive approach supported by quantitative data and was conducted in two cycles involving planning, action, observation, and reflection. The participants were Grade VII students of SMPN 1 Masbagik in the 2025/2026 academic year. Data were collected through observation, tests, and documentation. The findings revealed that the See, Think, Wonder strategy improved students’ critical thinking skills, as reflected in their enhanced ability to observe, question, analyze information, express logical opinions, and draw conclusions based on evidence. Students’ learning outcomes on fiction and nonfiction book materials also improved across the two cycles. The study concludes that the See, Think, Wonder strategy is effective in enhancing students’ critical thinking skills and learning outcomes in Indonesian language learning.